Faktor-Faktor Yang Berhubungan Dengan Siklus Haid Tidak Teratur Pada Mahasiswi Kebidanan Poltekkes Kemenkes Jayapura - Muji Lestari; Fachry Amal (Poltekkes Kemenkes Padang, 2019)
Based on preliminary studies that have been carried out on Jayapura Midwifery students, the results of 30 people who have experienced menstruation, 20 people said the menstrual cycle is irregular and 10 people said the menstrual cycle is regular. The purpose of this study was to determine the relationship between nutritional status and sports activities with menstrual cycles in midwifery students Department Poltekkes Jayapura. Type of research is quantitative research using cross sectional design. The population is 385 female students and sample is 196 respondents. Technique sampling using simple random sampling. Data is presented by table and and narrative form, the statistikal test is chi-square.The results of bivariate analysis using the chi-square test showed that there is a relationship between nutritional status and the menstrual cycle (ρ=0.008) and there is no relationship between sport activities with the menstrual cycle (ρ = 0.790). Suggestions for students to consume foods that have a balanced nutritional value, routinely do sports activities and avoid stress.